HYPERANDROGENISM IN PEDIATRICS − CLINICAL MANIFESTATIONS AND APROACH - Faria, Hugo de Castro; Amaro, Cristina (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Hyperandrogenism is common among teenagers, causing great psychological and social impact and may have underlying conditions that require specific medical intervention often multidisciplinary. The authors review the pathophysiology, clinical manifestations, differential diagnosis and therapeutic alternatives. We also propose a model of diagnostic approach according to their clinical presentation and therapy.